BLINDHEDENSAKUSTISKE HORISONTER: Om auditive kundskaber og en akustisk virkelighed - Lundberg, Pia (Tidsskriftet Antropologi, 2006)
With reference to the pioneering research of the few anthropologists, who have made sound an object of analysis, the article presents the author’s research in a blind community, thereby calling to attention sound, soundscape, sound-knowledge and sound-skills. The author takes a point of departure in empirical data from her fieldwork among blind children and youth in Denmark 2000-2005. An example of the research field is the virtual world of a computer game for the blind, which shows the difficulty of grasping the reality of the surrounding world, when this reality consists of sound and sound materiality. The article proposes that the players of the computer game create soundscapes, for example, how a pole by the road utters a kind of pole speech, or that a farmhouse in the Wild West makes its presence through significant farm-acoustics. In addition to new insights on blindness, the blind lifeworld and other perceptual horizons and skills, the study offers a cultural, scientific opening into objectifying both sound and sound perception as cultural phenomena, hence to expand an understanding of sound, acoustics and the auditory.